Regenerative and sustainable futures for Latin America and the Caribbean : collective action for a region with a better tomorrow - Gonzalez-Perez, Maria Alejandra (Emerald Publishing Limited, 2022)
The third decade of the 21st century brings new and expansive global sustainability challenges. Managers, policymakers, academics, citizens, and consumers will have to make seemingly contradictory decisions to accelerate demand, and at the same time promote savings. For this reason, it is necessary to clarify that it is not a process of recovery but of regeneration, adaptation and reprioritization. Regenerative and Sustainable Futures for Latin America and the Caribbean: Collective action for a region with a better tomorrow offers a systematic review of past efforts to recover from global crises providing an analysis of the sustainable development challenges faced by Latin America and the Caribbean. Featuring contributions from researchers in seven different Latin American and Caribbean countries, this volume reflects primary data perspectives from government, business, academe and civil society leaders in each specific country. Regenerative and Sustainable Futures for Latin America and the Caribbean explores how to build sustainable futures for Latin America and the Caribbean, presents recommendations for policy and decision-makers to thrive sustainable futures for Latin America and the Caribbean and reflects on the value of collective action for a region that deserves a better tomorrow.
Keywords: Environmental policy -- Latin America.; Environmental policy -- Caribbean.; Sustainable development -- Latin America.; Sustainable development -- Caribbean.; Political Science -- Public Policy -- Environmental Policy.; Environmental policy & protocols.; elektronické knihy; electronic books